Historical Reality as an Integral System in the Context of the Development of Kazakh Culture and Islamic Traditions - Aitbayeva, Bakyt; Karybaeva, Sayagul; Mirzahmetov, Almaz; Toleubayeva, Kamzhat; Zharmaganbetova, Ainash (Journal of Al-Tamaddun, 2024)
This study examines the issues of historical reality as an integral system in the context of the development of the Kazakh culture of epic singing and versification. Songs from a certain era were the recognition of historical moments such as the “national catastrophe” of the XVIII century, reflecting the opposition to the colonisation of the XIX century and the participation of famous historical figures in the 1916 national liberation uprising. The purpose of this study is to investigate the Kazakh folk epic poetry represented by legends, songs and poems, which reflect the various cultural events of the Kazakh historical reality of national evolvement and development. The primary approach used in this study is the combination of a systematic analysis of the materials from Kazakh national song and poetic culture with the logical development of the results and conclusions of this study. The main results of this study are the establishment of the conditional reliability of the events described in historical poetry. Assessing the historical reality of a single state in general and Kazakhstan in particular, one should consider the fact that not all historical events that have taken place were reflected in the works of national poets and became part of the national epic poetry. The various historical events and circumstances that occurred in the country throughout its history should also be considered. The prospects for subsequent study in this area are determined by the importance of studying the origins and traditions of the folklore of the Republic of Kazakhstan as the historical reality of the development of the state, which forms an integral system of the historical existence of the Kazakh people. The practical significance of this study lies in its potential to apply its findings to achieve a comprehensive understanding of specific phases in the evolution of Kazakh song and oral folklore, within the broader context of Kazakh cultural traditions.